Interpreting Philippians 4:5 in the efforts to strengthen the moderate attitude of the Christians in Indonesia - Saragih, Aditya Anugrah (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2025)
This study aims to analyze the contribution of Philippians 4:5 in strengthening religious moderation among Indonesian Christians, particularly in addressing intolerance, radicalization, and social tension within a pluralistic society. Employing a qualitative method and hermeneutical approach, the research explores the theological significance of the term epieikēs in Pauline theology and its relation to the principles of religious moderation in public policy and education. The findings reveal that epieikēs is not merely an individual virtue but a public and intersubjective ethical principle that can serve as a foundation for harmonious interfaith relations. This study affirms that integrating religious moderation values derived from Philippians 4:5 into government policy, religious education, and interfaith praxis can enhance social cohesion and enrich Christian public theology with socially relevant insights. The study contributes to the discourse on public theology, interreligious studies, and value-based policy formulation in religiously diverse societies. Contribution: It highlights the significance of epieikēs as a public and intersubjective ethical principle that extends beyond individual virtue, providing a foundation for fostering tolerance, mitigating radicalization, and reducing social tensions in a pluralistic context.